Oxidative stress, antioxidants, and reproductive problems during the pandemic (clinical lecture) - Vladimir V. Borisov (LLC "MEDIAFORMAT", 2021)
Oxidative stress (OS) results from imbalance between the inherent production of reactive oxygen species (ROS) and the capture of ROS by natural antioxidants in the living organism, as well as from failure of antioxidant systems involving cells' exposure to excess levels of ROC, molecular oxygen or its active forms (free radicals). Pathologic conditions result in imbalance between the quantity of ROC and free radicals produced, and the possibilities of their utilization. Consequently, free radicals, that the antioxidant systems have been unable to neutralize, damage cell structures (membranes, mitochondria, DNA, etc.). These processes occur both in germ cells (sperm, oocytes), and spermoplasm. In fact, a number of recent studies have confirmed that COVID-19 is a gender-related disorder: most patients with severe infection are males. Studying the viral entry mechanism has revealed that it may cause the profound damage to cells of reproductive system, and lead to delayed reproductive function impairment in young men and adolescents. Vitamin and mineral supplementation with optimum proportion of ingredients may be used as an efficient reinforcement for therapy aimed at fertility preservation and restoration in the current context of the pandemic.